Peculiarities of the English and Russian psychological novel - Yusupova, Sitora Ashuraliyevna; Khalliyeva, Gulnoz Iskandarovna (The Lingua Spectrum, 2026)
The psychological novel occupies a significant place in nineteenth-century realist literature due to its profound exploration of human consciousness, emotions, and moral experience. Although the phenomenon of literary psychologism has been extensively studied in both Russian and Western literary scholarship, comparative analyses of the English and Russian psychological novel remain relatively limited. This article examines the distinctive features of these two literary traditions by comparing their approaches to representing the inner world of the individual. The research is based on comparative, comparative-historical, hermeneutic, and textual analysis methods. The findings demonstrate that the English psychological novel is characterized primarily by indirect psychologism, revealing character through dialogue, behavior, symbolic detail, and interaction with the social environment. In contrast, the Russian psychological novel emphasizes direct psychological analysis, internal monologue, moral reflection, and philosophical inquiry. The study concludes that both traditions made a substantial contribution to the development of the psychological novel, enriching realist literature through different yet complementary artistic models of psychological representation.